Supramolecular structure of Artocarpus heterophyllus Lam seed starch prepared by improved extrusion cooking technology and its relationship with in vitro digestibility. (30th January 2021) - Li, Bo; Zhang, Yutong; Xu, Fei; Khan, Muhammad Rafiullah; Zhang, Yanjun; Huang, Chongxing; Zhu, Kexue; Tan, Lehe; Chu, Zhong; Liu, Aiqin
Highlights: Effect of IECT on supramolecular structure of jackfruit starch (JFSS) was studied. Mw, Rg, Rc of JFSS were notably decreased and amylose content wasn't changed by IECT. B2 and B3+ chains of JFSS were converted to A and B1 chains after IECT treatment. The mechanism of JFSS treated by IECT is break of α-1.4-glycosidic bond in backbone. In vitro digestibility of JFSS was improved by changes of supramolecular structure. Abstract: Jackfruit seed starch (JFSS) was modified by an improved extrusion cooking technology (IECT), and the supramolecular structure, molecular weight, debranched chain length distributions, relative crystallinity (Rc), and amylose content, were studied. During IECT, the α-1.4-glycosidic bond in amylopectin was broken, which led to decreased radius of gyration (Rg), number-average molar mass (Mn), weight-average molar mass (Mw), long chains and Rc. The medium and short chains and PI (Mw/Mn) increased, while the amylose content hardly changed. The crystalline structure of JFSS was converted from A-type to V-type. Increasing the temperature and screw speed during the treatment significantly increased the medium and short chains and Rg, while it decreased the long chains, amylose, Mn, Mw, PI, and Rc. However, the opposite effect was observed when increasing the moisture content. The in vitro digestibility of JFSS was significantly improved after IECT, due to destruction of starch supramolecular structure according to principal component analysis.